PENGARUH PARTISIPASI MASYARAKAT TERHADAP KINERJA BADAN PENYELENGGARA JAMINAN SOSIAL (BPJS) KETENAGAKERJAAN KOTA DENPASAR - Sumawidayani, Nyoman; Suprilyani, Ni Wayan; Sastra Wijaya, Komang Adi (CITIZEN CHARTER, 2018)
ABSTRACT The Effect of Public Participation on the Performance of the Employment Social Security Organizer Agency (BPJS-Employment) of Denpasar The performance of BPJS-employment is not maximal so that there is a need of public participation to improve performance of BPJS-employment. The finding of the results of simple linear regression test showed that public participation influenced the performance of Employment Social Security Organizer Agency (BPJS-Employment) of Denpasar with regression coefficient score of 0.835, which means that if there is 1% increase of public participation then the performance of the agency will increase 0.835 point. Keywords: Public Participation, Performance